Sources of quartz grains influencing quartz cementation and reservoir quality in ultra-deeply buried sandstones in Keshen-2 gas field, north-west China. (December 2018) - Shi, Hui; Luo, Xiaorong; Yang, Haijun; Lei, Ganglin; Tang, Yangang; Zhang, Likuan; Lei, Yuhong
Abstract: Quartz cementation is a critical factor in the reservoir quality of ultra-deeply buried sandstones because of the high temperature and high-pressure at great depths. Therefore, determining the main influences retarding the growth of the quartz overgrowths is important for predicting the sweet spots of tight gas sandstones. The vast Keshen-2 gas field in Kuqa Depression is typical of such ultra-deep gas fields, despite the porosity and permeability of the target sandstones in the Lower Cretaceous Bashijiqike Formation being less than 10% and 0.5 md, respectively. The main gas reservoirs had been buried previously to a depth of 7000 m, with the maximum fluid temperature approaching 160 °C, in which authigenic quartz cements are extremely common. The heterogeneity of the physical properties and quartz cementation was investigated using core analysis, log interpretation, thin sections and scanning electron microscopy (SEM). The findings indicated that the Bashijiqike Formation could be stratified into upper porous and lower tight zones. The porosity of the sandstones in the upper zone is generally higher than 5% and abundant polycrystalline quartz grains are present. However, the reservoirs in the lower zone with low overall porosity values below 5%, contain high contents of monocrystalline quartz grains. The polycrystalline quartz grains show brown cathodoluminescence that indicates mainly a metamorphic source from the southern Tianshan provenance which is located to the north of Keshen-2. The monocrystalline quartz grains display primarily blue to violet luminescence colours, suggesting an origin from volcanic or plutonic mother rocks of the Wensu and Kuluketage provenance areas, situated to the southwest and southeast, respectively. The monocrystalline quartz grains are surrounded commonly by quartz overgrowths, whereas the polycrystalline quartz grains are cemented slightly. The presence of polycrystalline quartz grains hampers potential quartz overgrowths—the critical reason preserving the intergranular pores in the ultra-deeply buried sandstones of this gas field. Accordingly, we propose that the metamorphic quartz grain content is the main factor inhibiting quartz cementation, which preserves reservoir quality. This knowledge is conducive to determining the growing mechanism of high-quality reservoirs and predicting the sweet spots of gas production in the ultra-deeply buried sandstones. Highlights: Heterogeneities in reservoir quality and quartz cementation were investigated. Polycrystalline quartz grains restricted overgrowths as preserving primary pores. A provenance transformation was proposed in the Bashijiqike Formation.